Formação de educadores de jovens e adultos no Programa Geração Cidadã: relação entre saberes na proposição curricular - Pinheiro, Rosa Aparecida (2007)
This paper deals with the fundamental elements of a curricular proposal aiming at the formation of alphabetizers of young and adults, as long as it concerns the relation between the academic knowledge and that one arising from the classroom experience. The empirical field of the research comes from the work of the teachers responsible for the formation of the alphabetizers of the GerAção Cidadã Program (2004-2005) linked, as an Extension Program, to Federal University of Rio Grande do Norte. Indeed, it tries to understand how these young and adult educators makers figure out the link between the experienced knowledge, which their lives give testimony of, with the scientific knowledge, which they are entitled to mediate in class. This work is funded in the principles of the Collaborative Research, which constitutes a kind of qualitative research. It makes use of procedures supported by qualitative research, especially those ones related to reflexive sessions, as well as to documental researches and semi-structured interviews. These spaces have afforded the group of alphabetizers the opportunity to talk over their practice, not only individually but also collectively, in order to work out contributive proposals having in view changes in the educative actions. As elaborated contributions, we present a discussion about the specificities in the making of educators to EJA, in their differentiated social roles. Reflecting on the experiences of the educators makers, we highlight those elements we regard as essential to the constitution of a formation proposal, like formative times and spaces, dialogue and social memory. The curricular organization is compreneded as part of an enlarged dimension that does not restraint itself to school; rather, it is visualized as a structuring instance that connects different knowledge surpassing community and university. Under this optics, we come to the conclusion that the connection the scientific knowledge establishes with the experienced one, which is immersed in the cultural practices of those who are involved in the formative process, is the basement to a curricular proposal of a formation course destined to educators committed with the need of changing society